Rapid synthesis: Examining care coordination in the home-and community-care sector - Waddell, K; Moat, KA; Lavis, JN (My University, 2023)
An in-depth synthesis of what is known based on the best available global research evidence (i.e., evidence syntheses) and local research evidence (i.e., single studies) and may include a scan of experiences from other countries and from Canadian provinces and territories, about care coordination in the home-and community-care sector in response to a decision-maker's request.
Keywords: care; coordination; home; community; sector